2013
DOI: 10.1186/1742-4690-10-44
|View full text |Cite
|
Sign up to set email alerts
|

Forced virus evolution reveals functional crosstalk between the disulfide bonded region and membrane proximal ectodomain region of HIV-1 gp41

Abstract: Background: The disulfide-bonded region (DSR) of HIV-1 gp41 mediates association with gp120 and plays a role in transmission of receptor-induced conformational changes in gp120 to gp41 that activate membrane fusion function. In this study, forced viral evolution of a DSR mutant that sheds gp120 was employed to identify domains within gp120-gp41 that are functionally linked to the glycoprotein association site. Results: The HIV-1 AD8 mutant, W596L/K601D, was serially passaged in U87.CD4.CCR5 cells until replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…This would also explain why saturation of the mutant spike by 10E8 does not fully block 2F5 neutralization and why the effect also occurs with ligands that bind distal to 10E8. Flexibility of the MPER [19] would presumably allow propagation of conformational changes to other regions of Env upon antibody binding; functional links between the MPER, NHR and DSL regions have also been described [65] , [66] . MPER mutations might also lead to an exchange of the MPER between adjacent subunits and membrane.…”
Section: Discussionmentioning
confidence: 99%
“…This would also explain why saturation of the mutant spike by 10E8 does not fully block 2F5 neutralization and why the effect also occurs with ligands that bind distal to 10E8. Flexibility of the MPER [19] would presumably allow propagation of conformational changes to other regions of Env upon antibody binding; functional links between the MPER, NHR and DSL regions have also been described [65] , [66] . MPER mutations might also lead to an exchange of the MPER between adjacent subunits and membrane.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that loss of the V1 glycans at Asn 136 or Asn 141 /Asn 142 brings about changes in the gp120 -gp41 association site (96). We have also found that restoration of infectivity to a defective DSR double mutant (W596L and K601D) involves a D674E mutation in the MPER (58). These results suggest that the 136/142 glycans in V1 are allosterically linked to the function of the DSR, which is in turn linked to the function of the MPER.…”
Section: Role Of the Hiv-1 Gp41 Membrane-proximal Region In Infectionmentioning
confidence: 92%
“…1, C and D). By contrast, very little virus production was observed for the W596L/K601D (WLKD) mutant that lacks gp120 association (58), indicating that a fusion-competent glycoprotein complex is required for virus transmission in cultures initiated by cell-free and cell-associated virus. Because VSV G-pseudotyped WLKD virions are fully competent to initiate infection (see Fig.…”
Section: Role Of the Hiv-1 Gp41 Membrane-proximal Region In Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of these mutations will have neutral or negative effects on viral fitness, a small subset of these mutations may prove beneficial and enhance the ability for certain variants to replicate despite selective pressures of interest such as the host immune response or an antiviral drug. Forced adaptation experiments have been used to determine viral mutations that facilitate escape from drugs [4][5][6], monoclonal antibodies [7,8], host restriction factors [9][10][11], and species variation in host receptors [12][13][14] and to elucidate various viral mechanisms of infection and replication [15][16][17].…”
Section: Introductionmentioning
confidence: 99%